Three-Dimensional Characterization of Pores in Ti-6Al-4V Alloy - Baldisser, Marcia Regina; Rios, Paulo Rangel; Oliveira Hein, Luis Rogerio [UNESP]; Zschommler Sandim, Hugo Ricardo (Universidade Federal de São Carlos (UFSCar), Dept Engenharia Materials, 2011)
The direct three-dimensional characterization of opaque materials through serial sectioning makes possible to visualize and better quantify a material microstructure, using classical metallographic techniques coupled with computer-aided reconstruction. Titanium alloys are used as biomaterials for bone implants because of its excellent mechanical properties, biocompatibility and enhanced corrosion resistance. The Ti-6Al-4V alloy (in wt. (%)) with porous microstructure permits the ingrowths of new-bone tissues improving the fixation bone/implant. This is important to understand connectivity, morphology and spatial distribution of pores in microstructure. The Ti-6Al-4V alloy compacts were produced by powder metallurgy and sintered at three distinct temperatures (1250, 1400 and 1500 degrees C) to obtain distinct microstructures in terms of residual porosity. The visualization of the reconstructed 3D microstructure provides a qualitative and quantitative analysis of the porosity of Ti6Al4V alloy (volume fraction and pore morphology).
Keywords: 3D characterization; serial sectioning; titanium alloys